Goliath strikes back : how traditional retailers are winning back customers from ecommerce startups - Cohan, Peter S., 1957- (Apress, 2020)
Capturing the ecommerce edge in customer growth and retention has been a decades-long battle between eRetail startups and large traditional retailers. The two face different sets of challenges and those challenges are constantly evolving in our digital world. Goliath Strikes Back: How Traditional Retailers Are Winning Back Customers from Ecommerce Startups expands on this current industry shift in one of the most accessible, intriguing business books in recent times. Each chapter covers a different industry, as diverse and eclectic as consumer electronics, newspapers, groceries, logistics, and more. By looking at how traditional retailers are facing off against internet startups, you can gauge the landscape and form your own strategies. Author Peter S. Cohan expertly guides you from one case study to the next and makes topics enthralling even for the non-industry layperson. Goliath Strikes Back helps executives create an effective strategy in the modern ecommerce realm. Business professionals and outside enthusiasts alike are in for fascinating insights from Cohan about the mindsets and strategies of successful companies and their leaders. Changing strategies on a dime has always been essential in commerce, and never more so than in ecommerce's industry overhaul. Don't get left behind.